The Effectiveness Of Exercise Therapy And Ergonomic Seat Design In Controlling Low Back Pain (LBP) In Batik Craftsmen - Budi Aswin; Sri Astuti Siregar; Usi Lanita; La Ode Reskiaddin (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Occupational safety and health of workers in the informal sector, for example batik craftsmen, have a great risk of experiencing health problems due to work, one of the problems that is often encountered is the case of low back pain. This study aims to analyze the effectiveness of exercise therapy and ergonomic seating design as an effort to control cases of low back pain (LBP) in batik craftsmen. The research is a randomized controlled trial (RCT) design. The population in this study were all batik craftsmen in Danau Teluk District as many as 30 people and were also used as research samples. The data will be analyzed using an unpaired T-test with (? = 0.05). The results of the study p value = 0.000 which still means that there are differences in cases of low back pain in batik craftsmen with the provision of exercise therapy (exercise). The conclusion of exercise therapy (exercise) is effective in minimizing cases of low back pain in batik craftsmen.